Phosphorus recovery from high solid content liquid fraction of digestate using seawater bittern as the magnesium source. (1st January 2023) - Pepè Sciarria, T.; Zangarini, S.; Tambone, F.; Trombino, L.; Puig, S.; Adani, F.
Graphical abstract: Highlights: Struvite crystallization can take place even using high total solids digestate. Seawater bittern can be used as alternative source Mg 2+ source. Struvite can be a substitute of chemical fertilizers in agronomic test. Seawater bittern can improve downstream transferability of struvite precipitation. Abstract: Phosphorus recovery from digestate is considered a challenge because the possible discharge can lead to eutrophication. This study focuses on phosphorus recovery as struvite from the liquid fraction of swine manure digestate at a high total solids concentration, by using a lab-scale crystallizer operated in continuous mode (7 L·d −1 ). A by-product of salt production (seawater bittern, SWB) was assessed as Mg source for the formation of struvite instead of a chemical dosage (MgCl2 ) within a circular economy approach. Different Mg/P (1.8:1; 2:1; 3:1) ratios and different TS contents (TS 3.5 and 4.5 %) were studied. The maximum P recovery of 85 % and N recovery of 52 % was obtained at 4.5 % of TS and Mg/P ratio of 2:1, corresponding to an overall P and N recovery on the raw digestate of 70 % and 46 %, respectively. The presence of struvite was confirmed by X-ray diffraction (XRD) and scanning electron microscopy (SEM-EDS). Dried samples were then used as fertilizer in agronomic pot tests using Brassica rapa chinensis . Struvite obtained, showed comparable fertilizing properties in comparison with conventional fertilizers in terms of P (Mineral 5.6 ± 0.4; Poultry 5.7 ± 0.2; Struvite 5.9 ± 0.1 g kg −1 ), N and total biomass content such as chlorophylls ratio. The growth tests confirmed the possible use of struvite recovered as competitive alternative to conventional chemical phosphate fertilizers. The results showed that it can be possible to promote sustainable P recovery from high solids digestates by the combination of crystallizer reactor and Mg-salt byproducts.